Effect of multiple pregnancy and laterality on infant neurodevelopment. (12th December 2022) - Figueras, Maria; Cabot, Rosabel; Viñes, Maricarmen; Torres, Ximena; Martinez-Portilla, Raigam J.
Abstract: Objective: The objective of this study is to investigate the effect of type of pregnancy (singleton, dizygotic, and monozygotic) on infant neurodevelopment and to explore how laterality operates in this relationship. Methods: We constructed a prospective cohort of low-risk women with singleton, monozygotic, and dizygotic pregnancies. Laterality was evaluated using the Edinburgh's scale of laterality, while neurodevelopment was assessed using the Ages & Stages Questionnaire (ASQ). The confounding, modifying, and mediating effect of laterality on the relationship between multiple pregnancy and neurodevelopment was explored by linear regression. Results: We included 207 singletons, 77 dizygotic, and 75 monozygotic pregnancies. The mean age (SD) at assessment of neurodevelopment was 48.5 (7.5) months. There was a significant trend to poorer neurodevelopment across singleton, dizygotic and monozygotic pregnancies in communication (52.2, 47.6 and 42.3; p  < .001) and fine movements (49.6, 44.5 and 35.2; p  < .001) even after adjusting for confounders. As compared to singletons, both dizygotic (39.6% vs. 22.7%; p  < .001) and monozygotic (39.3% vs. 22.7%; p  < .001) pregnancies had a higher frequency of non-right laterality. Laterality was not associated with neurodevelopment, nor confounded, mediated or modified the effect of multiple pregnancy on neurodevelopment. Conclusion: The association of multiple pregnancy to poorer neurodevelopment was independent of children laterality.